Analyzing occupational lung disease among turquoise miners - M.J. Fahool; S. Masoodi; SM. Ehteshamfa; E. Rafeemanesh; M. Majdi (Salāmat-i kār-i Īrān, 2009)
Background and aims   Low dose and long term exposure to inorganic, organic, irritant and allergic substances in workplaces can slowly and gradually cause chronic diseases such as chronic bronchitis ,asthma and pneumoconiosis. The purpose of this study is the exact determination of  lung diseases prevalence in Turquoise Miners and determination of associated factors in these diseases.   Methods   In this cross-sectional survey, 117 of retired and present workers of Nishabour Turquoise Mine were studied about lung diseases. Data was collected by using respiratory questionnaire, interview, lung examination, spirometry, chest X-Ray and Manto test.   Results   Mean age of workers was 42.9, Experience mean was 11.5 years.7 workers suffered from simple silicosis and one worker suffered from PMF. All of patients had been retired.  Abnormal spirometry was presented in 30/3% that 25% of them were obstructive, 4% of were restrictive and 13% of them were mixed.   Conclusion   The results of this survey show that exposure to silica dust besides of silicosis, causes obstructive lung diseases. Because of cureless complications and permanent disability of this disease, preventive measures in mines especially primary preventive measures are effective methods for prevention that must be considered by employee, employers and occupational health specialists.